Determinação analítica e estudo da liberação in vitro de meloxicam em comprimidos - Oliveira, Érika De Fátima Silva (2009)
Meloxicam is a nonsteroidal anti-inflammatory drug (NSAID) used to relieve the signs and symptoms of osteoarthritis and rheumatoid arthritis in adults. No official method is available for the assay of drug in pharmaceutical formulations. The aim of this study was to develop and validate analytical methods for meloxicam quantification in tablets and then establish conditions for accomplishment of the test of dissolution of meloxicam tablets 15 mg. A spectrophotometric method was proposed employing two solvents: methanol and 0.1 M sodium hydroxide. Absorbances were performed at 356nm and 362nm, respectively. In addiction to spectrophotometric, an HPLC method was proposed for the estimation of meloxicam in tablets (mixture of pH 4.5 potasium phosphate buffer and acetonitrile 60:40, v/v, as mobile phase, UV detection at 364 nm, C18, 3 mm column, to 30ºC, run at a flow rate of 1 mLmin-1 and retention time around 2.6 min). To establish the conditions for accomplishment of the test of meloxicam dissolution were employed the reference product and products tests A and B. Several parameters were tested, the use of pH 7.5, 0.02 M phosphate buffer (900mL, to 37 ºC ± 0.5 ºC) as dissolution medium, paddle method (apparatus 2) and stirring speed of agitation of the dissolution medium of 100 rpm and collect time in 60 minutes were considered satisfactory. The samples were quantified by UV spectrophotometric method at 362 nm. In relation to the dissolution kinetics all of the products presented kinetics of first order. For the dissolution efficiency values were of 83.25 %, 83.73 % and 88.10 % for the A, B and reference products, respectively. The factors f1 and f2 were calculated demonstrating there to be similarity of the appraised medicines. The dissolution procedure in the conditions selected and the proposed methods can be used for quantification of meloxicam in tablets with selectivity, linearity, precision, accuracy and robustness.